In silico study of Impatiens balsamina L. for the screening of bioactive compounds as novel matrix metalloproteinase-1 inhibitor against photoaging - Sindi Fujiyanti; Mochamad Nurcholis (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Photoaging is skin aging caused by exposure to UV rays, which increases the expression of matrix metalloproteinase-1 (MMP-1). The photoaging process is related to the degradation of collagen types I and III in the extracellular matrix by MMP-1, which causes wrinkles on the skin. MMP-1 inhibitors from natural products have the potency as anti-photoaging. This study aims to screen the potency of bioactive compounds from Impatiens balsamina L. as MMP-1 inhibitors through in silico studies. The best test ligands were selected based on bioavailability, pharmacokinetics, toxicity, and molecular docking tests against the targetÂ protein MMP-1 (PDB ID: 1HFC)Â compared to that of control ligands (PLH and doxycycline). Peonidin, kaempferol, and pelargonidin were selected as the best test ligands because they accomplish the characteristics of bioavailability, pharmacokinetics, and toxicity. Based on molecular docking results, those test ligands have better binding affinity than that of control ligands, as indicated by rerank scores of -108.807 kcal/mol, -99.9796 kcal/mol, and -98.9128 kcal/mol, respectively. Those test ligands also formed the same interactions with control ligands at residues Ala182, Asn180, Glu219, and Leu181. The results suggest peonidin, kaempferol, and pelargonidin were candidates for anti-photoaging agents through MMP-1 inhibition.